Potential Role of Pain Catastrophic Thinking in Comorbidity Patients of Depression and Chronic Pain - Chen, Yuanyuan; Ju, Peijun; Xia, Qingrong; Cheng, Peng; Gao, Jianliang; Zhang, Loufeng; Gao, Hua; Cheng, Xialong; Yu, Tao; Yan, Junwei; Wang, Qiru; Zhu, Cuizhen; et al. (Frontiers in Psychiatry, 2022)
Background: Although comorbidity of depressive disorder (MDD) and chronic pain (CP) has been well studied, their association with pain catastrophizing is largely elusive. The present study aimed to investigate the potential effects of pain catastrophizing in patients with a comorbidity. Methods: 140 participants were included in this study and divided into three groups according to the Diagnostic and Statistical Manual of Mental Disorders and the International Association for the study of pain (the comorbidity group: depression patients with chronic pain, n=45; depression group: depression patients without chronic pain, n=47; healthy controls: n=48). The HAMD-24 and HAMA-14 were used by professional psychiatrist to evaluate the severity of depression and anxiety. Beck Depression Inventory-Ⅱ (BDI-Ⅱ) and Beck Anxiety Inventory (BAI) were conducted by patient self-report to assess symptom severity. Pain intensity numerical rating scale (PI-NRS) was to assesses pain intensity. Pain Catastrophizing Scale (PCS) and Pain Anxiety Symptoms Scale (PASS) were used to estimate pain-related negative thinking. Results: The results showed that PASS and PCS scores were significantly different among the three groups. Particularly, the scores in the comorbidity group were highest. Pearson correlation analysis revealed positive correlation between PCS (including the patients’ helplessness, magnification, rumination, and total scores) and the severity of depression symptoms, anxiety symptoms as well as pain intensity (P<0.05). Stepwise regression analysis further demonstrated that the total PCS score, high monthly income level and BDI score had positive impacts on PASS (P<0.05). We also found that total BDI score, disease course ≥ 1 year and pain intensity had positive effects on PCS (P<0.05), whereas years of education (≤12 years) had a negative effect on PCS (P=0.012). In all, we have clearly demonstrated that PCS and PASS could serve as potentially predictive factors in patients suffering from comorbidity of MDD and CP. Conclusion: Our results suggested the pain related catastrophic thinking and anxiety were more severe in the comorbidity group than in MDD only group and healthy group. Pain related catastrophizing thoughts and anxiety may have potentially effects on the comorbidity of depression and chronic pain.